Antibacterial Activity of Parijoto (Medinilla speciosa Blume) Fruit Against Serratia marcescens and Staphylococcus aureus - Tiana Milanda; Keri Lestari; Nimas T. I. Tarina (Indonesian Journal of Pharmaceutical Science and Technology, 2021)
Parijoto (Medinilla speciosa Blume) is a plant found in Mount Muria, Kudus, Central Java. The local community often uses its fruit to treat various diseases, as well as antibacterial, anti-inflammatory, antioxidant, and anti-cancer. This study aimed to determine the antibacterial activity of n-hexane, ethyl acetate and methanol extract from parijoto fruit against Staphyococcus aureus ATCC 29213 and Serratia marcescens clinical isolates. Gradual maceration of simplicial and antibacterial activity testing of the extracts was performed, followed by determining the Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC) and comparative antibacterial activity most active extract against ampicillin and cefadroxil. The results showed that all extracts exhibited activity against S. aureus ATCC 29213, but only ethyl acetate and methanol extracts had activity against S. marcescens clinical isolates. The highest antibacterial activity was shown by the methanol extract, which was more effective against S. aureus ATCC 29213, having the largest inhibition diameter and lowest MIC and MBC values (6.25 and 12.5 mg/mL). The comparative analysis indicated that the methanol extract demonstrated lower antibacterial activity against S. aureus ATCC 29213 than cefadroxil (72,511: 1). This antibacterial activity is presumed to be generated from alkaloids, polyphenols, tannins, flavonoids, quinones and saponina in the extract.Keywords: Amoxicillin, Cefadroxil, MIC, MBC